The Phillips Curve in Portugal - Rosa, Agostinho S. (2013)
This paper estimates the Phillips curve in Portugal using the Johansen Method, with the wage inflation rate as a dependent variable, based on annual data from the period 1954-1995. The main conclusions are as follows. Firstly, in the long term, the wage inflation rate relates positively to the inflation rate and negatively to the unemployment rate, as expected. There is also a positive relationship between the wage inflation rate and the average labour productivity growth index. Secondly, in the short term, the variation of the wage inflation rate relates negatively and significantly to the error correction mechanism with a negative unitary coefficient; therefore, there is a quick and significant response to the equilibrium error between the wage inflation rate and its determinants. Besides this adjustment, the wage inflation rate responds positively to a lagged wage inflation rate. The variation in the unemployment rate and the average labour productivity growth present the expected signal, negative and positive respectively, but without significance in the short term. The dummy that refers to the April 1974 revolution is significant.